# Solve for u -16/(u+3)=-8/u -16u+3=-8u
Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.
(-16)⋅u=(u+3)⋅(-8)
Solve the equation for u.
Multiply -16 by u.
-16u=(u+3)⋅(-8)
Simplify (u+3)⋅(-8).
Apply the distributive property.
-16u=u⋅-8+3⋅-8
Simplify the expression.
Move -8 to the left of u.
-16u=-8⋅u+3⋅-8
Multiply 3 by -8.
-16u=-8u-24
-16u=-8u-24
-16u=-8u-24
Move all terms containing u to the left side of the equation.
Add 8u to both sides of the equation.
-16u+8u=-24
Add -16u and 8u.
-8u=-24
-8u=-24
Divide each term by -8 and simplify.
Divide each term in -8u=-24 by -8.
-8u-8=-24-8
Cancel the common factor of -8.
Cancel the common factor.
-8u-8=-24-8
Divide u by 1.
u=-24-8
u=-24-8
Divide -24 by -8.
u=3
u=3
u=3
Solve for u -16/(u+3)=-8/u

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top